Ethyl 3-ethoxycarbonylmethyl-7-methyl-5-phenyl-5H-thiazolo[3,2-a]pyrimidine-6-carboxylate - Nagarajaiah, H. (International Union of Crystallography, 2012)
In the title compound, C20H22N2O4S, the central pyrimidine ring incorporating a chiral C atom is significantly puckered and adopts a slight boat conformation with C atom bearing the phenyl ring and the N atom opposite displaced by 0.367 (2) and 0.107 (2) Å, respectively, from the plane formed by the remaining ring atoms. The benzene ring is positioned axially to the pyrimidine ring, making a dihedral angle of 88.99 (5)°. The thiazole ring is essentially planar (r.m.s. deviation = 0.0033 Å). In the crystal, pairs of C—H⋯O interactions result in centrosymmetric dimers with graph-set motifs R 1 2(7) and R 2 2(8). A weak C—H⋯π contact is also observed.